The Influence of Lifestyle and Financial Literacy on Saving Behavior with Self-Control as a Moderating Variable: A Study on Young Workers - Nesia, Inggit Lufita Nur Hikmatul; Sartika, Farahiyah (International Journal of Economics Development Research (IJEDR), 2024)
The aims of this research is to identify the factors that influence the saving behavior of young employees in Nganjuk Regency. The factors examined include lifestyle and financial literacy, with self-control serving as a moderating variable. A total of 130 young workers in Nganjuk Regency participated in the study through questionnaires. This research employs a quantitative approach, utilizing SPSS 25 for analysis. The results indicate that lifestyle positively impacts saving behavior and has a significant influence, while financial literacy does not affect saving behavior. Furthermore, the findings reveal that self-control does not effectively moderate the relationship between lifestyle and saving behavior, but it does moderate the impact of financial literacy on saving behavior. Overall, this research emphasizes the importance of self-control, a healthy lifestyle, and a solid understanding of financial literacy in enhancing the saving behavior of young workers in Nganjuk Regency.